Methodology For Processing Images From Optical Observations And Photometry In Astronomy Course Laboratory Workshops - Sheroz Eraliyevich Nurmamatov (Euro Asian Journal Publishing, 2024)
In this work, a methodology for processing and photometry of images obtained from optical observations in laboratory classes of the astronomy course was developed. The main goal of the work is to correctly calibrate the data obtained from the observation processes, reduce noise, and determine the physical properties of astronomical objects using photometry. During the image processing, bias, dark, and flat field calibrations were performed. Using photometry, the brightness and color indices of objects were determined, and the classification and evolutionary state of stars were studied. During the work, modern software was used to increase the accuracy and reliability of observation results. This methodology is intended for practical application in astronomy laboratory classes and serves to develop the skills of students and researchers in analyzing observational data
Keywords: Astronomy; Optical observations; Image processing